Development of Problem-Based Learning Models in Strengthening Positive Character and Behavior of Early Childhood Students - Ramang, Ramang; Ahyani, Nur; Fitria, Happy (Journal of Social Work and Science Education, 2024)
The research aims to find out whether the Problem-Based Learning learning model can strengthen the positive character and behavior of students in early childhood education. The method used is Research and Development through observation, questionnaires, interviews, and documentation in the form of photos and videos. The results of the research show that using the Problem-Based Learning learning model in Early Childhood Education can strengthen the character of students in having faith and devotion to God Almighty and having noble, creative, cooperative, and independent morals. Apart from that, students can behave positively by tidying up the place, after carrying out activities, saying thank you for the help received, saying sorry if they make a mistake, and being able to clean the school environment with the result that 1.23% of students have not developed, 17.28% are starting to develop, 41.98% developed as expected, and 39.51% developed very well.